Strategic Insights into Financial Management Challenges Faced by SMES (Journal of Informatics Education and Research, 2024)
Micro, Small, and Medium-Sized Enterprises (MSMEs) are acknowledged as drivers of socioeconomic development and are essential to GDP growth, employment generation, and the encouragement of innovation and entrepreneurship. This is applicable to both established and developing economies, with special attention to the role that MSMEs play in the Indian economy. These labor-intensive organizations play a major role in preserving socioeconomic balance. But in developing countries like India, MSMEs' top issue is getting financing, which is why this study aims to highlight the difficulties small businesses confront. Utilizing a quantitative approach, the research identifies five distinct challenges as access to bank credits, strategic financial management, liquidity crunch, non-availability of other credit, poor management of finance encountered by MSMEs in India. The report emphasizes how important it is for people to have access to financing in order to promote entrepreneurship and boost economic growth. Encouraging the start of new entrepreneurial endeavors while facilitating timely access to funding becomes essential for the survival and further expansion of micro, small, and medium-sized businesses. The purpose of this research is to examine the obstacles MSMEs face in obtaining financing.